Athletic Pubalgia (Sports Hernia): Narrative Review of Pathophysiology, Diagnosis, and Management - Sadowski, Krzysztof; Modelska, Julia; Jeleń, Anita; Podolska, Anna; Paluchowicz, Karolina; Siwicka, Katarzyna; Szewczyk, Konrad; Janasik, Laura; Kociucka, Patrycja (Quality in Sport, 2026)
Background. Athletic pubalgia is a frequent yet poorly defined cause of chronic groin pain in athletes. It is not associated with a true inguinal hernia but results from overload-related injury to the musculotendinous and fascial structures responsible for pelvic and core stability. Heterogeneous terminology and diagnostic uncertainty lead to delayed diagnosis and inconsistent treatment strategies. Aim. To synthesize current evidence regarding the pathophysiology, diagnostic approach, and management strategies for athletic pubalgia. Materials and methods. A narrative review of the literature was conducted using PubMed, Google Scholar, and Scopus databases. English-language studies published after 2000 and involving adult populations were included, with a focus on etiology, clinical presentation, imaging, conservative treatment, surgical techniques, and rehabilitation protocols. Results. Available evidence indicates that athletic pubalgia is primarily caused by an imbalance between the abdominal wall and hip adductor musculature, leading to chronic overload of the pubic symphysis complex. Clinical diagnosis remains challenging due to overlapping symptoms with other causes of groin pain. Magnetic resonance imaging plays a key role in confirming characteristic musculotendinous injuries and excluding alternative diagnoses. Conservative treatment is recommended as first-line therapy. Surgical intervention provides higher success rates and a more reliable return to sport in patients with persistent symptoms. Conclusions. Athletic pubalgia is a complex, multifactorial condition requiring a comprehensive diagnostic and therapeutic approach. While rehabilitation is fundamental in initial management, surgery offers superior outcomes in refractory cases, highlighting the need for high-quality prospective studies to standardize diagnostic criteria and treatment algorithms.